Wastepaper Modernism - Rosenberg, Joseph Elkanah (Oxford University Press USA - OSO, 2021)
Wastepaper Modernism traces how 20th-century writers imagined the fate of paper at the dawn of a new media age. Cover – Wastepaper Modernism: Twentieth-Century Fiction and the Ruins of Print – Copyright – Dedication – Acknowledgments – Contents – List of Figures – Introduction: Reams and Tatters – The Old Medium – Muddy Palms – Hides and Hints and Misses in Print – The Historic Page – Chapter 1: Henry James's Literary Remains – Little Scraps – Uncommunicating Communication – A Taste for Waste – A Practical Plea for the Superficial – A Boxful of Ghosts – The Palpable Past – The Responsibility of Destruction – Chapter 2: Elizabeth Bowen's Junk Mail – A Messy Desk – Bad Epistolarity – Envelopes –
Description based on publisher supplied metadata and other sources
Keywords: Fiction-20th century-History and criticism; Modernism (Literature)-History; Paper in literature; Electronic books